From Archeology to Epistemology of Scenic Dance in Costa Rica - Avila Aguilar, Marta (2002)
This article aims to start a path towards the epistemology of Costa Rican dance since at this time, we consider that a large number of choreographic works have been performed during the 20th century. The national dancers have reached a good level in their corporal executions. It is time to give contributions from another side of the issue.